Analysis of Fin Tip Temperature and Fin Efficiency for Different Fingeometries and Materials Using Abaqus - Imran, S.; Noor, F.; Ali, H.; Hussain, A.; Ali, Z.; Shad, R. (The Nucleus, 2015)
Fins are widely used in various engineering applications to enhance the rate of heat transfer. The effect of fin geometry and its material on the fin efficiency and the amount of heat transferred are investigated in this study. Rectangular and triangular fin geometries have been considered and two fin materials, aluminum and carbon steel, have been selected. It is found numerically that the fin tip temperature and the fin efficiency are decreased with the increase of the convective heat transfer coefficient. ABAQUS has been used to conduct this numerical study.